Chlorhexidine for meatal cleaning in reducing catheter-associated urinary tract infections: a multicentre stepped-wedge randomised controlled trial. Issue 6 (June 2019) - Fasugba, Oyebola; Cheng, Allen C; Gregory, Victoria; Graves, Nicholas; Koerner, Jane; Collignon, Peter; Gardner, Anne; Mitchell, Brett G
Summary: Background: Evidence for the benefits of antiseptic meatal cleaning in reducing catheter-associated urinary tract infection (UTI) is inconclusive. We assessed the efficacy of 0·1% chlorhexidine solution compared with normal saline for meatal cleaning before urinary catheter insertion in reducing the incidence of catheter-associated asymptomatic bacteriuria and UTI. Methods: A cross-sectional, stepped-wedge, open-label, randomised controlled trial was undertaken in Australian hospitals. Eligible hospitals were Australian public and private hospitals, with an intensive care unit and more than 30 000 hospital admissions per year. Hospitals were randomly assigned to an intervention crossover date using a computer-generated randomisation system. Crossover dates occurred every 8 weeks; during the first 8 weeks of the study, no hospitals were exposed to the intervention (control phase), after which each hospital sequentially crossed over from the control to the intervention every 8 weeks. Patients requiring a urinary cathetwer were potentially eligible for inclusion in this hospital-wide study. Participants were excluded if they were younger than 2 years, had a medical reason preventing the use of the chlorhexidine, had the catheter inserted in theatre, did not have the catheter insertion date documented, required in-and-out or suprapubic catheterisation, had symptoms and signs suggestive of UTI at the time of catheter insertion, or were currently undergoing treatment for UTI. The intervention was the use of 0·1% chlorhexidine solution for meatal cleaning before urinary catheterisation with 0·9% normal saline used in the control phase. Masking of hospitals was not possible because it was not feasible to mask staff administering the intervention. The co-primary outcomes were the number of cases of catheter-associated asymptomatic bacteriuria and UTI per 100 catheter-days and were assessed within 7 days of catheter insertion in the intention-to-treat population. This trial is registered with Australian New Zealand Clinical Trials Registry, number ACTRN12617000373370. Findings: 21 hospitals were assessed for eligibility between Jan 5, 2017, and May 1, 2017; of these, three were successfully enrolled and randomised to one of three intervention crossover dates. 1642 participants in these hospitals were included in the study between Aug 1, 2017, and March 12, 2018, 697 (42%) in the control phase and 945 (58%) in the intervention period. In the control period, 13 catheter-associated UTI and 29 catheter-associated asymptomatic bacteriuria events in 2889 catheter-days (0·45 catheter-associated UTI cases and 1·00 catheter-associated asymptomatic bacteriuria cases per 100 catheter-days) were recorded compared with four catheter-associated UTI and 16 catheter-associated asymptomatic bacteriuria events in 2338 catheter-days (0·17 catheter-associated UTI cases and 0·68 catheter-associated asymptomatic bacteriuria cases per 100 catheter-days) during the intervention period. The intervention was associated with a 74% reduction in the incidence of catheter-associated asymptomatic bacteriuria (incident rate ratio 0·26, 95% CI 0·08–0·86, p=0·026), and a 94% decrease in the incidence of catheter-associated UTI (0·06, 95% CI 0·01–0·32, p=0·00080). There were no reported adverse events. Interpretation: The use of chlorhexidine solution for meatal cleaning before catheter insertion decreased the incidence of catheter-associated asymptomatic bacteriuria and UTI and has the potential to improve patient safety. Funding: HCF Research Foundation.